EFEKTIVITAS DRY NEEDLING TERHADAP INTENSITAS NYERI DAN RANGE OF MOTION PASIEN NYERI MYOFASCIAL TRIGGER POINTS OTOT TRAPEZIUS - Dessy Rakhmawati Emril,* Fadli Syahrul,* Nur Astini* (NEURONA, 2016)
INTRODUCTION MYOFASCIAL TRIGGER POINTS MTRPS IS DEFINED AS HYPERIRRITABLE SMALL SPOTS WITHIN TAUT BAND OF SKELETAL MUSCLES WHICH SUFFERED FROM INJURY OR EXCESSIVE WORKLOADS THE TRAPEZIUS MUSCLES CAUSED PAIN MOSTLY AROUND NECK AND SHOULDER DRY NEEDLING DN THERAPY USES FILIFORM NEEDLE TO TREAT MTRPS PAIN